A study of smartphone usage and barriers among the elderly - Mohd Mohadis, Hazwani; Mohamad Ali, Nazlena (IEEE Xplore, 2014)
A wide range of smartphone applications aimed at encouraging healthy diets and active lifestyles have been developed in recent years. However, the use of these smartphone applications among the elderly population that should benefit the most from them remains low. This paper reports on the barriers to smartphone usage among the elderly. In-depth interviews were conducted with the elderly to gather information about their demographics, experiences and the perceived barriers to using smartphones. Twenty-one participants were interviewed using a semi-structured interview method. Results show that the elderly have difficulties in using smartphones due to multiple reasons such as financial limitations, vision impairments, and lack of interest and knowledge in using technological devices and their advanced functionalities.